Paving materials and pavement analysis : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Huang, Baoshan (Geotechnical special publication ;, 2010)
Pavement Design And Paving Material Selection are important for efficient, cost effective, durable, and safe transportation infrastructure Paving Materials and Pavement Analysis contains 73 papers examining bound and unbound material characterization, modeling, and performance of highway and airfield pavements.